RESTORATION OF THE COVARIANT GAUGE a IN THE INITIAL FIELD OF GRAVITY IN DE SITTER SPACETIME - XIAO, CHEW YAN (2014)
Despite the fact that spacelike past infinity of de Sitter spacetime, the gravitational perturbation in de Sitter spacetime was reproduced via covariant retarded Green's function with covariant gauges /3 = 2/3 and a = 5/3 by taking into the account the non-vanishing contribution of initial data at Cauchy surface for a stationary mass particle M at the spatial origin moving along its geodesic that emanating from past infinity [1].